IMPLEMENTATION OF STUDENT-CENTRED LEARNING MODEL TO IMPROVE INDEPENDENCE AND 21ST CENTURY SKILLS - Agus Hidayat; Ismaul Fitroh; Moh. Imron Rosidi (Indonesian Journal of Education (INJOE), 2025)
This study aims to examine in depth the implementation of student-centred learning as a strategy to improve learning independence and 21st century skills. The method used is a literature review with a qualitative descriptive approach, utilising various recent academic sources such as scientific journals, books, and relevant conference proceedings. The findings indicate that student-centred learning is effective in developing independence by granting students autonomy to set goals, choose strategies, and evaluate their own learning. Additionally, this model has proven to support the mastery of 21st-century skills, such as critical thinking, creativity, communication, collaboration, digital literacy, and problem-solving abilities. Factors contributing to the successful implementation include the role of teachers as facilitators, the use of educational technology, and a collaborative and contextual learning environment. However, challenges remain, particularly regarding teacher readiness, resources, and student readiness differences. Overall, the implementation of student-centred learning is considered relevant to the demands of modern education and capable of making a significant contribution to the development of competent and adaptive independent learners in the global era.